Preparedness in Instructional Materials for the Implementation of the MTE Policy in Public Lower Primary School Education in Meru County, Kenya - Magaju, Jacinta Kagendo; Kubai, James; Kanyi, Charles (International Journal of Professional Practice, 2024)
In 2019, the Kenya Basic Education Curriculum Framework (BECF) introduced indigenous languages as a subject in lower primary education. Consequently, a policy was developed regarding the use of vernacular as an instructional medium for lower primary education. Nevertheless, there is uncertainty regarding the readiness of teaching and learning resources to support its implementation. This study aims to examine the influence of instructional materials on implementation of the MTE policy in lower primary school education in Meru County, Kenya. The study used a descriptive survey design, and adopted a mixed-method approach. The target population comprised 773 grade three class teachers and 773 head teachers. From this population, a sample of 155 head teachers and 155 grade three class teachers was selected through simple random sampling and purposive sampling techniques. Data was collected using questionnaires administered to grade three class teachers, and focus group discussions for the head teachers. A pilot study was conducted in Maara Sub-County in Tharaka-Nithi County. The reliability and validity of research instruments were ascertained; where the reliability of the data was ascertained by computing Cronbach’s Alpha coefficients which stood at 0.725. The quantitative data were analyzed using SPSS to derive descriptive statistics. Qualitative data was analyzed thematically. The findings revealed shortage of textbooks, reference materials, and instructional materials for teaching indigenous languages. Additionally, learners struggle with existing orthographies, while teachers encounter difficulties in utilizing available materials in language skills development. A significant correlation between preparedness in instructional materials and mother tongue policy implementation were noted. Adequate native language textbooks and learning materials are essential and stakeholders need to pprioritize instructional materials for successful execution of mother tongue language policy in lower primary. The study recommends pprovision of adequate and relevant resources to support MTE policy implementation.